STRATEGI BUMDES DALAM OPTIMALISASI EKONOMI DESA MELALUI PENGELOLAAN AGROWISATA D’GANJARAN KECAMATAN TAMAN KABUPATEN SIDOARJO - Nur Dilla Komalasari; Adi Susiantoro; Anggraeny Puspaningtyas (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Development in village areas aims to improve the welfare of rural communities and the quality of human life as well as reduce poverty through the provision of meeting basic needs, building facilities and infrastructure, developing local economic potential, and using natural resources and the environment in a sustainable manner. As for one of the strategies carried out by the government, namely establishing BUMDes where this institution is adjusted to the potential in each village. BUMDes Sambimadu is one of the BUMDes in Sidoarjo Regency which was established by the Sambibulu Village Government in 2017 where the name Sambi Madu stands for Sambibulu Maju and Unggul. However, researchers found a problem that occurred in BUMDes governance from an organizational structure that was still not optimal in managing existing business units, especially in D'Ganjaran agro-tourism and overlapping job descriptions of members resulting in overlapping jobs. Therefore this study discusses the BUMDes Strategy in Optimizing the Village Economy through D'Ganjaran Agrotourism Management, Taman District, Sidoarjo Regency. The purpose of this study is to analyze the BUMDes strategy in optimizing the village economy through D'Ganjaran agro-tourism, Taman District, Sidoarjo Regency. The method used is descriptive qualitative method with the approach of observation, interviews, documentation. The results of the research are improving coordination between the community, BUMDes, and the village government in the development of D'Ganjaran Agrotourism with periodic or spontaneous inter-agency meetings and also deliberations in forums then also through the Musrenbang.